2020
DOI: 10.1007/s11251-020-09502-9
|View full text |Cite
|
Sign up to set email alerts
|

Understanding instructional design effects by differentiated measurement of intrinsic, extraneous, and germane cognitive load

Abstract: Instructional design deals with the optimization of learning processes. To achieve this, three aspects need to be considered: (1) the learning task itself, (2) the design of the learning material, and (3) the activation of the learner’s cognitive processes during learning. Based on Cognitive Load Theory, learners also need to deal with the task itself, the design of the material, and the decision on how much to invest into learning. To link these concepts, and to help instructional designers and teachers, cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(73 citation statements)
references
References 42 publications
4
66
1
2
Order By: Relevance
“…We agree with authors such as Klepsch et al [29,30] that measuring a third, engagement-related construct is meaningful. That construct may not be a discrete source of cognitive load, however.…”
Section: Summary Of Recommendationssupporting
confidence: 87%
“…We agree with authors such as Klepsch et al [29,30] that measuring a third, engagement-related construct is meaningful. That construct may not be a discrete source of cognitive load, however.…”
Section: Summary Of Recommendationssupporting
confidence: 87%
“…However, none of these studies used a specific measure for germane load but only deduced their interpretation by combining measures of mental effort with learning outcome measures. Only in two studies reported by Klepsch and Seufert (2020), effects of germane load-inducing instructions were revealed by using the germane cognitive load scale of the differentiated questionnaire by Klepsch et al (2017). This leads to the assumption that if GCL increases, then the scores on the active load item should also increase, which gives us another scoring inference.…”
Section: How To Elicit and Validate Active And Passive Loadmentioning
confidence: 99%
“…Overall, there are several instructional means with which the different types of load can be elicited. Besides the theoretical arguments, there are also empirical studies confirming these effects, but only a few measured the effects with differentiated measures of load (e.g., Klepsch and Seufert, 2020).…”
Section: How To Elicit and Validate Active And Passive Loadmentioning
confidence: 99%
“…This is the reason why we investigated all the three types of load, as particularly these actively invested resources could be affected by social cues and the effects of gender similarity. Thus, with this differentiated measurement approach, we strive at specifying which aspects of the design affect which aspect of the cognitive affordances in terms of cognitive load (Klepsch and Seufert, 2020).…”
Section: Effects Of Speaker Gender When Learning From Instructional Videosmentioning
confidence: 99%